The phenolic profiles of Radix Tetrastigma after solid phase extraction (SPE) and their antitumor effects and antioxidant activities in H22 tumor-bearing mice. Issue 11 (18th September 2017) - Sun, Yong; Tsao, Rong; Chen, Fang; Li, Hongyan; Peng, Han; Jiang, Li; Chen, Yuhuan; Deng, Zeyuan
Abstract : Photographic illustrations of phenolic profiles, antitumor effects and antioxidant activities of Radix Tetrastigma after solid phase extraction (SPE) in H22 tumor-bearing mice. Abstract : Radix Tetrastigma (RT), a herbal medicine and functional food in China, showed strong antiproliferative activities in vitro . However, the effects and the underlying mechanism of phenolic-rich extract of RT in H22 tumor-bearing mice are still unknown. Thus, the phenolic profiles and antitumor/antioxidant activities of a solid phase extraction (SPE) semi-purified extract of RT were investigated by a combination of chemical assays, LC-QTOF-MS/LC-QqQ-MS techniques and a tumor-bearing mice model. As a result, the total phenolic/flavonoid contents (TPC/TFC) and 24 individual phenolics were identified and quantified, which showed higher contents than that of crude extract. Results also indicated that RT extract could inhibit tumor growth and induce apoptosis by regulating the expression of Bcl-2 family proteins and activating the caspase family proteins as well as suppressing tumor angiogenesis by inhibiting vascular endothelial growth factor (VEGF) expression. Besides, the interleukin-2 (IL-2) levels, tumor necrosis factor-α (TNF-α) production, CD4 + /CD8 + ratio, and NK cell levels were increased by RT administration, while RT significantly increased superoxide dismutase (SOD)/glutathione peroxidase (GSH-Px) activities and decreased malondialdehyde (MDA) content. Summarily, the findings clearly demonstrated that RT extract could inhibit tumor growth by inducing apoptosis and inhibiting angiogenesis as well as preventing cancer by improving the immune functions and antioxidant activities.